The 2024 clinical practice guidelines on the pharmacological management of Behavioural and Psychological Symptoms of Dementia (BPSD) in the Arab world - Syed Ali Bokhari; Tarik Qassem; Dania Al-Ayyat; Syed Fahad Javaid; Hamed Al-Sinawi; Walid Nasr (Middle East Current Psychiatry)
Abstract Background Over 90% of individuals living with dementia experience behavioural and psychological symptoms of dementia, like agitation, anxiety, delusions, and sleep disturbances, which complicate care and place significant demands on healthcare systems. These guidelines are designed to meet the unique needs of dementia care in the Arab world, where dementia rates are increasing due to an ageing population. Main body These clinical practice guidelines provide evidence-based guidance tailored to the Arab World, with a focus on minimising unnecessary psychotropic use in dementia. The guidelines advocate a multi-pronged strategy, prioritising non-pharmacological interventions which are often safer and align well with local values and caregiving practices. Pharmacological treatments are recommended only for severe cases where symptoms cause distress or pose a risk to the patient or others. The guidelines cover key medication classes with detailed recommendations on dosage, side effects, and monitoring. Conclusions By integrating culturally appropriate, evidence-based strategies, these guidelines aim to enhance dementia care quality, incorporate the perspectives of patients and caregivers, support healthcare professionals, and promote safer, more effective management of dementia across diverse healthcare settings in the region.